2019
DOI: 10.1038/s41598-019-40339-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA DSB Repair Dynamics following Irradiation with Laser-Driven Protons at Ultra-High Dose Rates

Abstract: Protontherapy has emerged as more effective in the treatment of certain tumors than photon based therapies. However, significant capital and operational costs make protontherapy less accessible. This has stimulated interest in alternative proton delivery approaches, and in this context the use of laser-based technologies for the generation of ultra-high dose rate ion beams has been proposed as a prospective route. A better understanding of the radiobiological effects at ultra-high dose-rates is important for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 38 publications
0
48
0
Order By: Relevance
“…Looking beyond the scope of our specific goals, recent works show a growing interest in radiobiological effects of high mean dose rate radiation 17,60 . From the presented results we expect to provide an attractive research platform to radiobiologists working on said topic in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking beyond the scope of our specific goals, recent works show a growing interest in radiobiological effects of high mean dose rate radiation 17,60 . From the presented results we expect to provide an attractive research platform to radiobiologists working on said topic in the future.…”
Section: Discussionmentioning
confidence: 99%
“…By that they have the potential for a wide range of multi-disciplinary applications. This includes warm dense matter research 4 , probing of ultra-fast plasma dynamics 5 , material research 6 and archaeological surveys 7 , injector sources for conventional accelerator structures [8][9][10] or radiobiology studies of laser-driven proton and ion beams [11][12][13][14][15][16][17][18] as well as translational research in laser-driven radio-oncology 19 . In general these applications require specific beam qualities, such as controlled spectral and spatial shapes, particle number as well as sufficient reproducibility and stability.…”
mentioning
confidence: 99%
“…For both hadron and electron beams, there is still much to understand with respect to the fundamental interaction between such ultrashort particle beams delivering doses at ultrahigh rates and biological tissue. 66 Laser-plasma accelerator radiotherapy studies can readily deliver the absorbed dose for patient treatment. 20,66 However, clearly the laboratory environment is not a clinical setting for patient trials.…”
Section: Application Programmesmentioning
confidence: 99%
“…66 Laser-plasma accelerator radiotherapy studies can readily deliver the absorbed dose for patient treatment. 20,66 However, clearly the laboratory environment is not a clinical setting for patient trials. This illustrates the proof-of-principle concept of the centre.…”
Section: Application Programmesmentioning
confidence: 99%
“…It has already been demonstrated that it is possible to use laser-accelerated protons for stress testing of materials 6 , investigation of cultural heritage 7 , as a front-end for conventional accelerators 8,9 or to probe transient electromagnetic fields with ps temporal and μm spatial resolution 10 . Potential future applications include biomedical ones such as hadron therapy 11,12 . For all these applications, a reliable and controllable source of energetic protons is crucial.…”
Section: Introductionmentioning
confidence: 99%